PERAN GURU DALAM MENINGKATKAN KARAKTER CINTA TANAH AIR MELALUI PEMBELAJARAN PKN di SDN PABUARAN - Fadil, Khaidir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to know the teacher's role in increasing the character of loving the motherland through learning citizenship education at SDN Pabuaran. This type of research is qualitative and uses a descriptive method. The aim is to explain the teacher's role in making students in Civics lessons more characterized by love for the motherland. The research subjects were students at SDN Pabuaran Cilendek, Bogor City. Researchers use primary and secondary data sources to collect information in this study. The primary data source is the class teacher assigned to teach Pkn topics. Secondary data used includes journals and books. Observation and interview are two data collection techniques. Miles and Huberman's interactive model analysis method is used in data analysis methods, namely data reduction, data visualization, and validation inference. The results of the study show that teachers need to play an important role in increasing the character of loving the motherland, giving direct examples of how to be proud of using domestic products such as batik clothes, giving examples of using Indonesian as the language of everyday communication properly and correctly, and introducing various cultures Indonesia as a form of love for the Indonesian homeland through the culture that exists in Indonesia and is a preservation of Indonesian culture